A meso-macroscopic constitutive model of frozen saline sandy soil based on homogenization theory. (August 2019) - Chang, Dan; Lai, Yuanming; Zhang, Mingyi
Highlights: The elastic parameters of equivalent inclusion phase of frozen saline soil are derived. A constitutive model of frozen saline sandy soil is proposed based on homogenization theory. The influences of plastic parameters on the constitutive behaviors are investigated. Abstract: As an effective multiscale method, homogenization theory is widely applied to the composite material research field. The saturated frozen saline sandy soil can be regarded as a typical kind of composite material composed of sandy soil matrix, ice, salt crystals and unfrozen water inclusions. A meso-macroscopic constitutive model of saturated frozen saline sandy soil is developed based on the homogenization theory. In the proposed model, the constitutive response of equivalent inclusion phase is presented by an elastic-brittle model while that of sandy soil matrix phase is described by a critical state elastoplastic model. Based on the three-phase sphere model and Mori-Tanaka method, the expressions of elastic parameters of equivalent inclusion phase are given. The influences of inclusion volume contents on elastic parameters of equivalent inclusion phase are analyzed. On the other hand, the plastic parameters of sandy soil matrix phase can have considerable effects on the macroscopic deformation features. Compared with the experimental results, the proposed model can predict the deformation of frozen saline sandy soil with different salt contents at various confining pressures. The strain hardening/softening, high dilation and pressure melting features can be well reproduced.